ANALISIS PENERAPAN PEMBELAJARAN BERDIFERENSIASI DALAM KURIKULUM MERDEKA PADA MATERI TATA SURYA DI KELAS VII SMP - Fitra, Devi Kurnia (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2022)
The implementaton of differentiated learning in the Independent Curriculum on the Solar System material in class VII SMP Negeri 1 Tembilahan is a Classroom Action Research conducted in two cycles to improve learning and student activity. Starting with a diagnostic assessment, the teacher can carry out learning according to the learning needs of students. From the results obtained a significant increase in student learning outcomes from the pre-cycle, cycle I and cycle II. Thus, differentiated learning is one of the definite learning approaches to the independent curicculum.